42.4k views
5 votes
S = kr^(2)+krl, for K

... I've been trying to solve it but I keep getting different answers. If someone can show me the steps in getting the answer; I'll appreciate it.

2 Answers

5 votes

Answer:

k = S/(r^2 + rl).

Explanation:

S = kr^(2) + krl

Factor the right side:

S = k(r^2 + rl)

Divide both sides by (r^2 + rl):

k = S/(r^2 + rl).

User Shokha
by
5.1k points
6 votes

Start with


S=kr^2+krl

Factor k on the right hand side:


S=k(r^2+rl)

Assuming
r^2+rl\\eq 0, divide both sides by this quantity:


(S)/(r^2+rl)=(k(r^2+rl))/(r^2+rl)

Simplify the right hand side:


(S)/(r^2+rl)=k

And thus we have solved the expression for k:


k=(S)/(r^2+rl)

User Suroor Ahmmad
by
5.5k points